Thailand Environment Monitor : Integrated Water Resources Management - A Way Forward - World Bank (World Bank, 2012)
Water is everyone's business. Beside a necessity for living, water has implications on public health and, most importantly, can cause social conflicts. This is because water is limited, is difficult to control, and can easily be polluted. The Integrated Water Resource Management (IWRM) process is considered worldwide as a means to reduce social conflicts from competing water needs as well as to facilitate effective and sustainable development of water resources. Effective implementation of IWRM however will require appropriate policy, regulation, and institutional frameworks which could facilitate cross-sectoral dialogue and cooperation among water users. A good example of IWRM is in the Lower Mekong River Basin. IWRM has been adopted by the Mekong River Commission (MRC) as a means to management water resources through the 1995 agreement, where as MRC countries are fully committed to manage water resources. In Thailand, IWRM has been technically recognized as a means to achieve sustainable water resources management and the concept has been incorporated in the national policy for more than 15 years, however clear institutional responsibility and introduction of the IWRM concept to local communities are relatively new. To address the challenges on water resource management in Thailand, particularly at the local level, stronger leadership and commitment of the key government agencies and effective cooperation of the water users will be important.